O sistema de inovação da Universidade Federal de Uberlândia da geração de conhecimento à transferência de tecnologia - Macêdo, Larissa Sarmento (2016)
It is known that in analogous way the developed countries, in Brazil, significant part of the technological innovation is originating from Public Institutions of Superior Teaching and Public Center of Inquiries through incitement of government agencies. In this perspective, a formation is necessary focused for the managers of the Agency of Technological Innovation (NITs) responsible for the partnerships and transfers of technology. The present inquiry aims to present the System of Innovation of the Federal University of Uberlândia (UFU). The central question concerns questionings on what the universities can do so that this knowledge developed by his investigators reaches the enterprises, becoming so effectively an Innovation. There was observed which the structure necessary so that a Nucleus of Innovation is success, models of management, legislation, team and strategies used with Nucleuses that stand out inside this sector. For such, there was diagnosed the reality of the business sector of the Directorship of Innovation and Transfer of Technology of the Institution (Agency Intellect), which answers like Nucleus of technological Innovation of the UFU, in parallel to Systems of Innovation that has renown in executing transfers of technology and of knowledges for the market. His strategies and policies of acting were analyzed, so, besides the importance of a gestor had been with profile and post-graduation aiming universities-enterprises implementing transfer of technology and of the ways of partnerships, exploring the benefits for both and the innovation production. In this perspective, this work touches in adjacent points to the Technological Innovation, of the means of transfer of technology and of the ways of partnerships universities-enterprises, exploring and when benefits are supporting what exists for both.